Carcass traits of young Simmental bulls and heifers classified according to the EUROP system - Karolyi, Danijel; Đikić, Marija; Salajpal, Krešimir; Čubrić Čurik, Vlatka; Jurić, Ivan (Acta Agraria Kaposváriensis, 2006)
The objective of this investigation was to determine the carcass traits (weight and measurements, dressing percentage, cooling loss, shares of separated fat and dissected muscle, fat, bone and tendon tissues as well as shares of beef cuts of different retail categories) of young Simmental bulls (n = 13) and heifers (n = 13) classified according to EUROP system which were produced as Croatian baby beef destined for Italian market. The classification showed a favorable conformation of both, bulls and heifers with about one third carcasses graded as highest E class. The heifers fatness was less favorable and almost half of carcasses were classified as high fat class (4) and thus less valuable. The heifers over fatness was confirmed by significantly higher amount of trimmed carcass fat and higher share of fat tissue and lower share of muscle than bulls after carcass dissection. The carcasses of both sex classified as most valuable E class had the lowest proportion of muscle which imply a need for a additional improvement of conformation assessment practice. The differences between bulls and heifers in dressing percentage, carcass cooling loss, shares of Milanese cut, bone and tendon tissue as well as shares of cuts of different beef retail categories in the carcass were relatively small.
Keywords: Simmental cattle; baby-beef; carcass traits; EUROP system